Dinamika Kepemimpinan dalam Pengambilan Keputusan di Tengah Disrupsi Digital dan Tekanan Opini Masyarakat: Suatu Tinjauan Literatur - Givanni Yoraysha Nabila; Indri Valensia Rahmadhani; Nurul Afri Dewi; Boni Saputra; Fachri Adnan (CV. ITTC INDONESIA, 2026)
The era of digital disruption has fundamentally transformed the landscape of organizational leadership. Leaders are now confronted with a dual complexity: managing internal technological transformation while simultaneously responding to intensifying public opinion pressure driven by social media penetration. This article presents a literature review of leadership dynamics within the context of digital disruption and public opinion pressure. By examining and synthesizing various internationally reputed academic literature from Scopus and Web of Science databases (2023-2025), this study identifies dominant themes, research gaps, and future research agendas. Thematic analysis reveals that: (1) digital leadership remains in a maturing phase as a scholarly field; (2) the integration of external pressure factors including public opinion dynamics into leadership models represents a critical unresolved gap; and (3) adaptive leadership grounded in emotional intelligence and transparency proves effective in crisis conditions. This study contributes a comprehensive synthesis and research roadmap for developing leadership models that are responsive to digital and social dynamics.